2006
DOI: 10.1002/eji.200536618
|View full text |Cite
|
Sign up to set email alerts
|

NFAT transcription factors in control of peripheral T cell tolerance

Abstract: The Ca ++ -regulated calcineurin/NFAT cascade is one of the crucial signalling pathways that controls adaptive immunity. However, a number of novel experimental data suggest that, in addition to their role in T cell activation, NFATc transcription factors play also a decisive role in the generation of peripheral tolerance against self-antigens. This function of NFATc factors is mediated by controlling activation-induced cell death and clonal anergy of T helper cells and the activity of regulatory T cells. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 65 publications
0
42
0
1
Order By: Relevance
“…This particular phenomenon has been accounted for by the downregulation of NFATmediated FasL expression, [26][27][28][29] leading to a lack of activated T-and B-cell apoptosis. 23 Consistent with this interpretation, NFATc2/c3 double-deficient T cells restimulated in vitro with anti-CD3 antibody do not die after 6 to 8 h, indicating that, unlike wild-type T cells, they do not undergo activation-induced cell death (AICD). 30 A similar proapoptotic function of NFATc2 has been described for Burkitt's lymphoma cells following B-cell receptor stimulation.…”
Section: The Death Of Cdcs After Activation Is Regulated By Nfatmentioning
confidence: 63%
See 1 more Smart Citation
“…This particular phenomenon has been accounted for by the downregulation of NFATmediated FasL expression, [26][27][28][29] leading to a lack of activated T-and B-cell apoptosis. 23 Consistent with this interpretation, NFATc2/c3 double-deficient T cells restimulated in vitro with anti-CD3 antibody do not die after 6 to 8 h, indicating that, unlike wild-type T cells, they do not undergo activation-induced cell death (AICD). 30 A similar proapoptotic function of NFATc2 has been described for Burkitt's lymphoma cells following B-cell receptor stimulation.…”
Section: The Death Of Cdcs After Activation Is Regulated By Nfatmentioning
confidence: 63%
“…Before our demonstration of a proapoptotic role for NFATc2/c3 in activated cDCs, a similar proapoptotic role had already been reported for these two isoforms in activated T and B lymphocytes. 23 NFATc2-deficient mice do indeed have considerably larger numbers of peripheral lymphocytes than wild-type mice. 24,25 This phenotype is even more marked in mice lacking both NFATc2 and c3, which also had markedly enlarged peripheral lymphoid organs.…”
Section: The Death Of Cdcs After Activation Is Regulated By Nfatmentioning
confidence: 92%
“…NFAT consists of four homologous NFAT1 (NFATc2), NFAT2 (NFATc1), NFAT3 (NFATc4), and NFAT4 (NFATc3) (Hogan et al, 2003;Macian, 2005;Serfling et al, 2006;Wu et al, 2007). Most of the NFAT genes are expressed in lymphocytes, however NFAT1 is predominantly expressed in naïve, single-positive T cells.…”
Section: +mentioning
confidence: 99%
“…In addition to anergy intrinsic to the T cell, NFAT proteins have been implicated in the regulation of gene expression of two other major mechanism of peripheral tolerance -T reg suppression and activation-induced cell death [22]. For instance, it has been reported that NFAT1 interacts with the transcription factor Foxp3 in the epigenetic regulation of genes involved in T reg differentiation.…”
Section: Transcriptional Regulation Of E3 Ligases In T-cell Tolerancementioning
confidence: 99%
“…Following costimulation, NFAT cooperates with the AP-1 family of transcription factors, and possibly others, to induce the expression of activation-associated genes [20,21]. In contrast to normal activation, anergic conditions appear to lead to an unbalanced activation of NFAT and translocation of NFAT proteins to the nucleus in the absence of AP-1, thereby inducing the expression of anergy-associated genes [15].In addition to anergy intrinsic to the T cell, NFAT proteins have been implicated in the regulation of gene expression of two other major mechanism of peripheral tolerance -T reg suppression and activation-induced cell death [22]. For instance, it has been reported that NFAT1 interacts with the transcription factor Foxp3 in the epigenetic regulation of genes involved in T reg differentiation.…”
mentioning
confidence: 99%